Piston ring oil film thickness measurements in a four-stroke diesel engine during steady-state, start-up and shut-down. (April 2023) - Rooke, Jack; Brunskill, Henry; Li, Xiangwei; Taghizadeh, Saeid; Hunter, Andy; He, Shan; Lu, Xiqun; Dwyer-Joyce, Robert S
Internal combustion engine research predominantly focuses on routes to lower emissions to meet various emission legislation. Lower emissions can be achieved with increased fuel efficiency and less lubricant throw off/lubricant combustion in the piston ring zone. These are all dependent on the oil film that forms between the liner and piston components. This article details the use of ultrasonic sensors to study the lubricant film thickness between the engine liner and piston rings/skirt in a fired diesel two-cylinder YTR engine. The testing regime covered a series of engine speeds and loading levels and found the minimum oil film thickness to vary from 1 to 3.5 μm. Spectrograms (time-varying ultrasonic amplitude spectra) have shown a residual oil film on the liner, first present after the skirt moves above the sensor that peaks at 440 μm, which then dissipates until the next oil control ring passage. Start-up and shut-down captures have visualised the build-up and reduction of the film thickness, in which during start-up typically a 2-s interval between the first ring passage and a consistent film thickness was seen. Whilst the shut-down tests showed a lesser variation, anticipated to be due to the oil pump already operating and is, therefore, less subjective to a reduction in engine speed providing a threshold of oil remains on the liner. Measurements like this help to describe how lubrication occurs in the piston ring zone and hence can optimise component design and an oil injection schedule.